Molecular mechanism on autophagy associated cardiovascular dysfunction in Drosophila melanogaster - Zhang, Wei; Zhou, Rong; Lei, Xinjuan; Wang, Mofei; Duan, Qinchun; Miao, Yuanlin; Zhang, Tingting; Li, Xinjie; Zutong, Zhang; Wang, Liyang; Jones, Odell D.; Xu, Mengmeng; et al. (Frontiers in Cell and Developmental Biology, 2025)
As a highly conserved cellular process, autophagy has been the focus of extensive research due to its critical role in maintaining cellular homeostasis and its implications in cardiovascular pathogenesis. The decline in muscular function, along with the neuronal system, and increased sensitivity to stress have been recognized in multiple animal models. Autophagic defects in cardiovascular architecture and cellular dysfunction have been linked to both physiological and pathological conditions of the heart in mammals and Drosophila. In this review, we systematically analyze the autophagy-associated pathways in the hearts of fruit flies and aim to provide a comprehensive understanding for developing potential treatments for patients and effective strategies for agricultural applications. This analysis elucidates the molecular mechanisms of autophagy in cardiovascular function under both physiological and pathological conditions in Drosophila, offering significant insights into the development of cardiovascular diseases. The loss of key autophagy-associated proteins, including the transmembrane protein Atg9 and its partners Atg2 or Atg18, along with DmSestrin, leads to cardiac hypertrophy and structural abnormalities in Drosophila, resembling the age-dependent deterioration of cardiac function. Members of the autophagy-related (Atg) gene family, cellular or nuclear skeletal lamins, and the mechanistic or mammalian target of rapamycin (mTOR) signaling pathways are critically influential in heart function in Drosophila, with autophagy activation shown to suppress cardiac laminopathy. The mTORC1/C2 complexes, along with axis of Atg2-AMPK/Sirt1/PGC-1α pathway, are essential in the hearts of both mammals and fruit flies, governing cardiac development, growth, maturation, and the maintenance of cardiac homeostasis. The beneficial effects of several interventions that enhance cardiac function, including exercise and cold stress, can influence autophagy-dependent TOR activity of the serine/threonine protein kinase signaling in both mammals and Drosophila. Exercise has been shown to increase autophagy when it is deficient and to inhibit it when it is excessive, highlighting the dual role of autophagy in cardiac health. This review evaluates the functional significance of autophagy in the heart, particularly in the context of Drosophila, in relation to mTORC-associated autophagy and the axis of Atg2-AMPK/Sirt1/PGC-1α pathways. It systematically contrasts the molecular mechanisms underlying autophagy-related cardiovascular physiological and pathological conditions in both fruit flies and mammals. The evolutionary conservation of autophagy underscores the value of Drosophila as a model for understanding broader mechanisms of autophagy across species. This study not only deepens our understanding of autophagy’s role in cardiovascular function but also provides a theoretical foundation for the potential application of autophagy in agricultural pest control.